B-cell Receptor Activation Induces BIC/miR-155 Expression through a Conserved AP-1 Element - Yin, Qinyan (2007)
microRNA-155 is an oncogenic microRNA that has been shown to be critical for B-cell maturation and immunoglobulin production in response to antigen. In line with its function in B-cell activation, miR-155, and its primary transcript, B-cell integration cluster (BIC), is induced by B-cell receptor (BCR) cross-linking. Using pharmacological inhibitors in the human B-cell line, Ramos, we show that activation of BIC and miR-155 expression by BCR signaling occurs through the extracellular signaling-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) pathways but not the p38 pathway. BCR activation results in the induction of c-Fos, FosB, and JunB, and expression of these are suppressed by ERK and JNK inhibitors. Reporter analysis established a key role for a conserved AP-1 site ∼40 bp upstream from the site of initiation but not an upstream NF-κB site or a putative c-Ets located at the site of initiation. Lastly, chromatin immunoprecipitation analysis demonstrated the recruitment of FosB and JunB to the miR-155 promoter following BCR activation. These results identify key determinants of BCR-mediated signaling that lead to the induction of BIC/miR-155.